Development of Digital Educational Media Based on Family For Improving Adolescent Self-Efficacy in Maintaining Reproductive Health : Literature Review - Siti Naili Ilmiyani; Nurlathifah N Yusuf; Ernawati (CV. Get Press Indonesia, 2024)
Self-efficacy of adolescents in guarding reproductive health is an important predictor of health behavior related to sexual decision safety and the prevention of risks such as sexually transmitted infections and unwanted pregnancy. Development of digital technology provides opportunities for developing interactive educational media that can be accessed by teenagers and their families to increase self-efficacy. This literature review analyzed 11 internationally published articles between 2016–2026 related to digital media-based reproductive health education interventions that involve family or social support, including mobile health (mHealth), interactive applications, social media, and web platforms. The results show that digital educational media is generally capable of increasing knowledge, attitudes, and confidence/self-efficacy of teenagers regarding reproductive health, especially when accompanied by family involvement or parental support. In conclusion, family-based digital educational media can become a potential strategy to strengthen adolescents’ self-efficacy in making healthy decisions related to reproductive health. However, further studies with stronger experimental designs are required.